An Analysis of Translation Ideologies on Andmesh Indonesian Song “Hanya Rindu” into English “Just Missing You” Emma Heesters - Desi.A.R. Simbolon; Susi Santrika Sitinjak; Yesica Hageltira Sitorus; Laminton Sihotang (Merwin Publisher, 2025)
This study analyzes the translation ideology behind the English rendition of the Indonesian song